The Development and Acceptability of a Psychology‐Based Intervention for Debilitating Symptom Complexes Attributed to Ticks. - Dharan, Anita L.; Yap, Valerie M. Z.; Kanaan, Richard A.; Oliver, Georgina; Sim, Yen D. Y.; Braat, Sabine; Cotter, Georgia; Chatterton, Mary Lou; Mihalopoulos, Cathrine; Wilson, Sarah J.; Chalder, Trudie (Health Expectations, 2026)
Background: Debilitating Symptom Complexes Attributed to Ticks (DSCATT) is a chronic, debilitating illness associated with tick bites in Australia. DSCATT is of unknown aetiology, can impact emotional well‐being and has no recognised treatments. Objective: The development and piloting of a novel psychotherapeutic adjunctive intervention for DSCATT that aimed to increase daily functioning, improve quality of life and reduce the impact of symptoms in people with DSCATT. Methods: This is a single‐site, intervention development and acceptability study. The intervention was developed iteratively according to a Human‐Centred Design (HCD) approach and manualised across four phases, with input from end users at each phase: qualitative interviews, development of the intervention, piloting, and revising and refining the intervention. Acceptability of the prototype intervention was evaluated through thematic template analysis of exit interviews. Self‐report measures were completed before and after intervention delivery. Results: Following qualitative interviews with 13 participants (11 females and 2 males; aged 35–70 years), the intervention was informed by an Acceptance and Commitment Therapy (ACT) model interwoven with cognitive and behavioural strategies that targeted DSCATT‐specific difficulties. The manualised intervention consisted of 12 1‐h weekly individual sessions, delivered by psychologists via Telehealth (video call or telephone). Modules addressed the six core psychological processes of ACT, alongside DSCATT‐specific modules addressing cognitive function, sleep and social relationships. Pilot testing and follow‐up interviews were conducted in a separate sample of six individuals with DSCATT (all females; aged 46–71 years). All participants reported that the approach benefited their emotional well‐being and overall health and would recommend it to others with DSCATT. Conclusions: This is a novel and theoretically driven psychotherapeutic intervention for DSCATT, co‐produced with patient involvement across four phases. Pilot testing suggested the manualised intervention was feasible and acceptable, supporting future evaluation of feasibility and treatment outcomes with randomised controlled trials. Patient or Public Contribution: This study involved the engagement and participation of individuals with DSCATT across four stages of the project, according to an HCD approach—the choice of the intervention; the development of the intervention; the piloting of the intervention, and the assessment of the intervention. Trial Registration: The pilot study component of this project was prospectively registered on the Australian and New Zealand Clinical Trial Registry (ANZCTR); trial ID: ACTRN12621001032842.